Rapid Pulsed-Field Gel Electrophoresis Method for Group B Streptococcus Isolates - Benson, Jeffrey A. (American Society for Microbiology, 2001)
We developed a rapid pulsed-field gel electrophoresis (PFGE) method that required 3 days to complete, an improvement over the standard method that required as many as 8 days. The accuracy and reproducibility of the rapid method were verified by analysis of DNA band sizes of our control group B streptococcus isolate. The rapid method was superior to the standard method, providing more precise molecular sizing and gels of higher image quality. The reproducibility of rapid PFGE substantiated its value and continued use.